Nu class glutathione S-transferase (GST) from the freshwater diatom Fragilaria saxoplanctonica: characterization and transcriptional responses to pollutant-induced oxidative stress - Jin-Joo Hong; Han-Sol Kim; Taehee Kim; Jang-Seu Ki (Molecular & Cellular Toxicology, 2026)

pH changes differently affect carbonic anhydrases (Ap-CAs) transcriptions in the marine toxic dinoflagellate Alexandrium pacificum - Han-Sol Kim; Jeongmin Shin; Taehee Kim; Jang-Seu Ki (Marine Environmental Research, 2026)

In vitro storage under slow growth, plant regeneration, and ex vitro acclimatization of Ligusticum officinale (Makino) Kitag - Ye-Won Kim; Han-Sol Lee; Hosakatte Niranjana Murthy; Hyoshin Lee; So-Young Park (South African Journal of Botany, 2026)

In vitro propagation of Cymbidium ‘Snow Pearl’ in semi-solid, liquid, and temporary immersion bioreactor system (TIS) cultures - Beomsoo Kang; Ye-Won Kim; Han-Sol Lee; Jong-Eun Han; Hosakatte Niranjana Murthy; Yae Jin Kim; Pil Man Park; So-Young Park (Horticulture, Environment, and Biotechnology, 2026)

Evaluation of two novel superoxide dismutases (SODs) from the freshwater diatom Fragilaria saxoplanctonica and their specific responses to metals and pesticides - Hee-Jin Kang; Han-Sol Kim; Taehee Kim; Jang-Seu Ki (Ecotoxicology, 2026)

Iron availability modulates ferric reduction oxidase (FRO) gene expression in the toxic dinoflagellate Alexandrium pacificum - Quynh Thi Nhu Bui; Han-Sol Kim; Sofia Abassi; Hee-Jin Kang; Jang-Seu Ki (European Journal of Protistology, 2026)

Circadian-dependent UV-B stress responses reveal differential antioxidant and photoprotective mechanisms in Achyranthes japonica microgreens - Ye Lin Kim; Han-Sol Sim; Jae Gil Yun; Ki-Ho Son (Molecular & Cellular Toxicology, 2026)

Multi-functional roles of cold shock protein genes (CSPs) in the toxic marine dinoflagellate Alexandrium catenella: assessment of cold, heat, and metal stress - Quynh Thi Nhu Bui; Han-Sol Kim; Jang-Seu Ki (Journal of Applied Phycology, 2026)

Effects of light-emitting diode (LED) light sources on in vitro protocorm-like body (PLB) proliferation, plantlet regeneration, and ex vitro acclimatization in Cymbidium ‘Snow Pearl’ - Beomsoo Kang; Ye-Won Kim; Han-Sol Lee; Jong-Eun Han; Hosakatte Niranjana Murthy; Yae Jin Kim; Pil Man Park; So-Young Park (Horticulture, Environment, and Biotechnology, 2026)

Exploring Cyclo (-Gly-Pro) for inflammation modulation in atopic dermatitis: a study on streptococcal postbiotics - Haeun Lee; Yunseok Oh; Tae-Won Seo; Young-Bong Choi; Sol Kim; Sejin Cheon; Dong-Geol Lee; Seunghyun Kang; Kyudong Han; Young Mok Heo; Seyoung Mun (Genes & Genomics, 2026)

Saxitoxin biosynthesis genes in the marine dinoflagellate Gymnodinium: Transcriptomes of toxic and non-toxic species and their environmental insights - Buhari Lawan Muhammad; Han-Sol Kim; Taehee Kim; Jang-Seu Ki (Harmful Algae, 2026)

Biological upcycling of conditionally biodegradable plastics: enzymatic depolymerization to microbial valorization and consolidated bioprocessing frameworks - Yunhee Jeong; Sol Min Han; Jieun Wu; KwangYoung Park; Yunjeong Song; Yung-Hun Yang; Kyung-Jin Kim; Jungoh Ahn; Kyungmoon Park; See-Hyoung Park; Si Jae Park; Eun Ju Yun; et al. (Systems Microbiology and Biomanufacturing, 2026)

Virucidal activity of Cannabis sativa L. (hemp) root and stem extracts against Japanese encephalitis virus: role of stigmasterol - Han-Sol Ryu; Ki-Hyun Kim; Kiu-Hyung Cho; Ah-Ra Lee; Sang-Uk Seo; Sejin Jeon; Sun-Woo Yoon; Sanghyun Lee; Yun Kwon; Yo Han Jang (Archives of Virology, 2025)

Robust Relative Space Motion Control of Underwater Vehicles Using Time Delay Estimation - Gun Rae Cho; Hyungjoo Kang; Min-Gyu Kim; Sungho Park; Chulhee Bae; Han-Sol Jin; Seongho Jin; Ji-Hong Li (Journal of Marine Science and Engineering, 2025)
This paper presents a robust trajectory-tracking control framework for underwater vehicles operating in a relative coordinate system. Unlike conventional methods that define trajectories in the world frame, the proposed approach formulates the control problem directly in a moving reference frame, enabling accurate motion control with respect to dynamic and drifting objects affected by environmental disturbances such as ocean currents and waves. This relative-space formulation is particularly advantageous for tasks including diver guidance, floating-object inspection, and docking, where the reference itself is nonstationary. A coordinate transformation is introduced to consistently express the vehicle dynamics in the relative frame. Based on the transformed dynamics, a Time Delay Control (TDC) law is applied to estimate unmodeled dynamics and external disturbances without requiring precise system parameters. Theoretical stability analysis shows that the stability condition of the proposed controller is consistent with that of conventional TDC, allowing similar gain-tuning procedures. Simulation results demonstrate that the proposed controller achieves robust and smooth trajectory tracking even when the reference frame undergoes motion induced by ocean currents.

Two chloroplast superoxide dismutase genes (MnSOD and CuZnSOD) in the freshwater dinoflagellate Palatinus apiculatus and their high-level gene expression in response to algicidal agents - Quynh Thi Nhu Bui; Han-Sol Kim; Jang-Seu Ki (Journal of Applied Phycology, 2025)

Transcriptomic comparison unveils saxitoxin biosynthesis genes in the marine dinoflagellate Gymnodinium catenatum - Buhari Lawan Muhammad; Han-Sol Kim; Quynh Thi Nhu Bui; Jang-Seu Ki (Harmful Algae, 2025)

Assessment of ship hull-attached marine diatoms: species composition and reattachment - Jaeyeong Park; Buhari Lawan Muhammad; Taehee Kim; Quynh Thi Nhu Bui; Han-Sol Kim; Kyoungsoon Shin; Bonggil Hyun; Jung-Hoon Kang; Jang-Seu Ki (Marine Pollution Bulletin, 2025)

Evaluating nuclear (18S, ITS, and 28S) and chloroplast (psbB, psbC, rbcL, and tufA) genes of the green algae Monoraphidium (Sphaeropleales, Chlorophyta) for DNA barcoding - Ha-Eun Lee; Taehee Kim; Han-Sol Kim; Ok-Min Lee; Jang-Seu Ki (Algae, 2025)
The genus Monoraphidium is a green microalgae distributed globally in freshwater ecosystems, and it is difficult to classify morphologically. Molecular genetic markers have been used for their taxonomy, although they have not been thoroughly evaluated. Here, we investigated three nuclear rRNA molecules (18S, internal transcribed spacer [ITS] + 5.8S, and 28S) and four chloroplast genes (psbB, psbC, rbcL, and tufA) using 16 Monoraphidium strains consisting of 9 species. Upon comparisons of genetic diversity and marker performance evaluation, we found that ITS was the best marker for Monoraphidium to discriminate each species, followed by tufA. The taxonomic discrimination power of the ITS was supported by the neighbor-joining tree. In addition, a secondary structure of ITS2 combined with compensatory base changes showed the distinct differences among individual species of Monoraphidium. These suggest that ITS may be the best marker for species differentiation of the coccoid green algae Monoraphidium.

Nitrogen (N) balancing metabolism in the toxic dinoflagellate Alexandrium pacificum against N shift revealed by physiology and N-related genes regulation - Han-Sol Kim; Sofia Abassi; Quynh Thi Nhu Bui; Jang-Seu Ki (Chemosphere, 2025)

Photosynthesis genes modulate cadmium tolerance in the freshwater alga Closterium acutum revealed by transcriptome analysis - Jeongmin Shin; Han-Sol Kim; Quynh Thi Nhu Bui; Taehee Kim; Jang-Seu Ki (Journal of Applied Phycology, 2025)

Scalable fabrication of a tough and recyclable spore-bearing biocomposite thermoplastic polyurethane - Han Sol Kim; Evan M. White; Grant Crane; Kush Patel; Myung Hyun Noh; Md Arifur Rahman; Adam M. Feist; Jason J. Locklin; Jonathan K. Pokorski (Chemical Engineering Journal, 2025)

Efficacy of Bone Regeneration Cell Therapy Using Mesenchymal Stem Cells Originating from Embryonic Stem Cells in Animal Models; Bone Defects and Osteomyelitis - Jin-Ho Park; Han-Sol Bae; Ingeun Kim; Jiwoon Jung; Yoonho Roh; Dongbin Lee; Tae Sung Hwang; Hee-Chun Lee; June-Ho Byun (Tissue Engineering and Regenerative Medicine, 2025)

Evaluation of acute, repeated dose 28-day and 13-week oral toxicity and genotoxicity of a standardized fraction (HemoHIM) from Angelica gigas, Cnidium officinale, and Paeonia lactiflora - Ju Gyeong Kim; Su-Bin Bak; Gyoung-Deuck Kim; Han-Sol Choi; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2025)
HemoHIM is a functional food ingredient comprising a triple herbal combination of extracts from Angelica gigas Nakai, Cnidium officinale Makino, and Paeonia lactiflora Pallas. It was developed to aid the recovery of impaired immune function. Although it is widely used to treat various immune disorders in Korea, its potential toxicity has not been extensively investigated. Therefore, a comprehensive study was conducted to assess the safety of HemoHIM, including acute oral dose toxicity, 28-day and 13-week repeated-dose toxicity, and genotoxicity. To evaluate its safety profile, the dose was increased to 2,000 mg/kg/day, which corresponds to the dose limit for acute toxicity as per the Organization for Economic Cooperation and Development Test Guideline 423. No abnormal findings were observed at the higher doses. For the 28-day and 13-week repeated-dose toxicity studies, HemoHIM was administered at doses of 500, 1,000, and 2,000 mg/kg/day to examine subchronic toxicity in male and female rats. No test item-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology evaluations further supported the safety of HemoHIM. Therefore, the NOAEL of HemoHIM was considered to be at 2,000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronucleus test were conducted to determine the genotoxicity of HemoHIM, which revealed that HemoHIM was non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence to support the safe use of HemoHIM as a functional food ingredient.

Adlercreutzia faecimuris sp. nov., producing propionate and acetate isolated from mouse feces - Min Kuk Suh; Jong- Sik Jin; Hyo Eun Do; Ji-Sun Kim; Mi Kyung Eom; Han Sol Kim; Jung- Sook Lee (Antonie van Leeuwenhoek, 2024)

Phocaeicola acetigenes sp. nov., producing acetic acid and iso-butyric acid, isolated faeces from a healthy human - Hyo Eun Do; Young Bong Ha; Ji-Sun Kim; Min Kuk Suh; Han Sol Kim; Mi Kyung Eom; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; et al. (Antonie van Leeuwenhoek, 2024)

Jatrophihabitans cynanchi sp. nov., isolated from rhizosphere soil of Cynanchum wilfordii - Min Kuk Suh; Ji-Sun Kim; Mi Kyung Eom; Han Sol Kim; Hyo Eun Do; Yong Kook Shin; Jung- Sook Lee (Antonie van Leeuwenhoek, 2024)

Full Coverage Path Planning for Torpedo-Type AUVs’ Marine Survey Confined in Convex Polygon Area - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Han-Sol Jin (Journal of Marine Science and Engineering, 2024)
In this paper, we present a full coverage path planning (CPP) algorithm for the marine surveys conducted in the convex polygon shaped search area. The survey is supposed to carry out by torpedo-type AUVs (autonomous underwater vehicles). Due to their nonholonomic mechanical characteristics, these vehicles have nonzero minimum turning radius. For any given polygon shaped search area, it can always be partitioned into one or more convex polygons. With this in mind, this paper proposes a novel search algorithm called CbSPSA (Calculation based Shortest Path Search Algorithm) for full coverage of any given convex polygon shaped search area. By aligning the search inter-tracks alongside the edge with the minimum height, we can guarantee the minimum number of the vehicle’s turns. In addition, the proposed method can guarantee the planned path is strictly located inside the polygon area without overlapped or crossed path lines, and also has the total path length as short as possible. Considering the vehicle’s nonzero minimum turning radius, we also propose a sort of smoothing algorithm which can smooth the waypoint path searched by CbSPSA so that the vehicle can exactly follow it. The smoothed path is also guaranteed to be strictly located inside the polygon. Numerical simulation analyses are also carried out to verify the effectiveness of the proposed schemes.

Significant Reduction of Photosynthesis in the Harmful Dinoflagellate Margalefidinium polykrikoides by Co-culturing with the Marine Green Alga Tetraselmis suecica - Han-Sol Kim; Buhari Lawan Muhammad; Jang-Seu Ki (Ocean Science Journal, 2024)

Promoter regions of sxtA and sxtG reveal relationship between saxitoxin biosynthesis and photosynthesis in toxic Alexandrium catenella - Han-Sol Kim; Quynh Thi Nhu Bui; Jeongmin Shin; Hui Wang; Jang-Seu Ki (Journal of Applied Phycology, 2024)

Polyphyletic origin of saxitoxin biosynthesis genes in the marine dinoflagellate Alexandrium revealed by comparative transcriptomics - Quynh Thi Nhu Bui; Han-Sol Kim; Jang-Seu Ki (Harmful Algae, 2024)

Development of saxitoxin biosynthesis gene sxtB-targeted qPCR assay for the quantification of toxic dinoflagellates Alexandrium catenella (group I) and A. pacificum (group IV) occurring in the Korean coast - Han-Sol Kim; Taehee Kim; Jaeyeon Park; Tae Gyu Park; Jang-Seu Ki (Harmful Algae, 2024)

Nuclear genome of dinoflagellates: Size variation and insights into evolutionary mechanisms - Hui Wang; Peiling Wu; Lu Xiong; Han-Sol Kim; Jin Ho Kim; Jang-Seu Ki (European Journal of Protistology, 2024)

Two novel glutathione S-transferase (GST) genes in the toxic marine dinoflagellate Alexandrium pacificum and their transcriptional responses to environmental contaminants - Hyunjun Park; Han-Sol Kim; Sofia Abassi; Quynh Thi Nhu Bui; Jang-Seu Ki (Science of The Total Environment, 2024)

Gordonibacter faecis sp. nov., producing urolithin C from ellagic acid, isolated from feces of healthy Korean subjects - Han Sol Kim; Ji-Sun Kim; Min Kuk Suh; Mi Kyung Eom; Hyo Eun Do; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; Jung-Sook Lee (Archives of Microbiology, 2024)

Isolation, culture of protoplasts of Angelica gigas Nakai and regeneration of plants via somatic embryogenesis - Han-Sol Lee; Jong-Eun Han; Eun Yee Jie; Suk Weon Kim; Hyuk Joon Kwon; Gun-Myung Lee; Hak Sung Lee; Hosakatte Niranjana Murthy; So-Young Park (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Effects of nitrate on the saxitoxins biosynthesis revealed by sxt genes in the toxic dinoflagellate Alexandrium pacificum (group IV) - Sofia Abassi; Han-Sol Kim; Quynh Thi Nhu Bui; Jang-Seu Ki (Harmful Algae, 2023)

Data-to-data translation-based nowcasting of specific sea fog using geostationary weather satellite observation - Yerin Kim; Han-Sol Ryu; Sungwook Hong (Atmospheric Research, 2023)

Disturbance observer-based nonfragile fuzzy tracking control of a spacecraft - Tae Joon Han; Han Sol Kim (Advances in Space Research, 2023)

Molecular cloning, origin, and expression of saxitoxin biosynthesis gene sxtB from the toxic dinoflagellate Alexandrium catenella - Han-Sol Kim; Quynh Thi Nhu Bui; Hui Wang; Jang-Seu Ki (Journal of Applied Phycology, 2023)

Comparative transcriptome analysis reveals the molecular mechanism of heat-tolerance in Neopyropia yezoensis induced by Sargassum horneri extract - Qikun Xing; Sol Han; Ji-Sook Park; Charles Yarish; Jang K. Kim (Frontiers in Marine Science, 2023)
Introduction Heat stress is one of the main threats for the seaweed aquaculture, leading to the decay of the blades and causing serious economic losses. A newly developed biostimulant, Sargassum horneri extract (SHE), can enhance the heat-tolerance in Neopyropia yezoensis, which can be applied in the seaweed aquaculture. However, the molecular mechanism underlying this acquired heat-tolerance is still unclear. Method In this study, we examined the transcriptional regulation of N. yezoensis under heat stress after the SHE pre-treatment by performing the RNA-Seq on illumina Novaseq platform and differentially expressed gene analysis. Result and discussion Our results show that, under heat stress, the SHE pre-treatment can alleviate the suppression of genes involved in normal cell activities, such as ribosome biogenesis, photosynthesis, respiration and cell cycle. On the other hand, SHE pre-treatment can also induce some key genes involved in the heat-tolerance. We also found that the combination of SHE pre-treatment and heat stress can induce some genes related to epigenetic modification, suggesting that SHE may facilitate the formation of heat stress memory in N. yezoensis. Our study provides information for understanding the molecular mechanism of heat-tolerance in N. yezoensis and for promoting the application of seaweed-derived biostimulants in the seaweed aquaculture.

Saxitoxins-producing potential of the marine dinoflagellate Alexandrium affine and its environmental implications revealed by toxins and transcriptome profiling - Han-Sol Kim; Hyunjun Park; Hui Wang; Taehee Kim; Jang-Seu Ki (Marine Environmental Research, 2023)

Hypoxia-alleviating hemoglobin nanoclusters for sensitizing chemo-photodynamic therapy of cervical cancer - Han Sol Lee; So-Yeol Yoo; Sang Min Lee; Nae-Won Kang; Sang Kyum Kim; Gyu Yong Song; Dae-Duk Kim; Jae-Young Lee (Chemical Engineering Journal, 2023)

Sargassum horneri and Ascophyllum nodosum extracts enhance thermal tolerance and antioxidant activity of Neopyropia yezoensis - Sol Han; Hye-In Song; Ji-Sook Park; Youn-Jung Kim; Schery Umanzor; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2023)

Low salinity causes oxidative stress and modulates specific antioxidant gene expression in the toxic dinoflagellate Alexandrium pacificum - Quynh Thi Nhu Bui; Han-Sol Kim; Jang-Seu Ki (Journal of Applied Phycology, 2022)

Adaptive Formation Control of Multiple Underactuated Autonomous Underwater Vehicles - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Gun Rae Cho; Han-Sol Jin (Journal of Marine Science and Engineering, 2022)
In this paper, we present a 3D formation control scheme for a group of torpedo-type underactuated autonomous underwater vehicles (AUVs). These multiple AUVs combined with an unmanned surface vessel (USV) construct a sort of star-topology acoustic communication network where the USV is at the center point. Due to this kind of topological feature, this paper applies a virtual school concept. This is a geometric graph where each node is taken as a virtual leader for each specific AUV and assigned its own reference trajectory. For each individual vehicle, its formation strategy is simple: just follow the trajectory of its corresponding virtual leader so as for multiple AUVs to compose the given formation. As for the formation subject, this paper mainly focuses on the formation tracking problem rather than the formation producing. For the torpedo-type vehicle considered in this paper, there are only three control inputs (surge force, pitch, and yaw moments) available for its underwater 3D motion and therefore this is a typical underactuated system. For the following vehicle’s trajectory, a sort of potential field method is used for obstacle avoidance, and a neural network-based adaptive scheme is applied to on-line approximate the vehicle’s unknown nonlinear dynamics, and the uncertainty terms including modeling errors, measurement noises, and external disturbances are handled by the properly designed robust scheme. The proposed formation method can guarantee the uniform ultimate boundedness (UUB) of the closed-loop system. Numerical studies are also carried out to verify the effectiveness of the proposed scheme.

Effect of Different Solvents on the Extraction of Compounds from Different Parts of Undaria pinnatifida (Harvey) Suringar - Hyun-Hwa Lee; Jin-Sol Kim; Jun-Han Jeong; Su Mi Park; Ramaraj Sathasivam; Sook Young Lee; Chun Sung Kim (Journal of Marine Science and Engineering, 2022)
Asian kelp (Undaria pinnatifida) is a brown alga mainly grown and consumed in East Asian countries such as China, Japan, and Korea. To date, studies on the various biological activities of Asian kelp have been conducted; however, studies focusing on the different parts of Asian kelp and their use for other than food are limited. Therefore, in this study, different parts of Asian kelp, namely, whole U. pinnatifida (UP), U. pinnatifida blade (UPB), U. pinnatifida stipe (UPS), and U. pinnatifida sporophylls (UPSP), were extracted by using different solvents including ethanol, methanol, and hot water. The antioxidant activity, antiaging effect, and phenolic content of the extracts were investigated. The results revealed that the UPB methanolic extract had significantly higher polyphenol and flavonoid contents, with the respective values of 5.61 mg TAN/g and 7.80 mg QUE/g, than the other extracts. The DPPH and ABTS radical scavenging activities and FRAP values were the highest in the 95% ethanolic (IC50 12.73 mg/mL), methanolic (63.83%), and ethanolic (75.75%) extracts of UPB, respectively. Superoxide dismutase, catalase, and ascorbate peroxidase enzymatic activities were also measured, and the results showed that the activities of these enzymes were higher in the UPB methanolic extract than in the other extracts. Similarly, the highest elastase and tyrosinase inhibitory activity was observed in the UPB methanolic extract. The highest phenolic content was found in the hot water extract of UP (4-hydroxybenzoic acid) and the ethanolic extracts of all parts (naringin and naringenin). The phenolic content of the Asian kelp differed depending on the parts and extraction solvents used. Finally, the antioxidant activity of the UPB extract showed a close correlation with the polyphenol and flavonoid contents. The methanol extract of UPB exhibited excellent antioxidant and antiaging activities, indicating its potential use in the development of functional materials using Asian kelp and in other new applications.

Bacteroides humanifaecis sp. nov., isolated from faeces of healthy Korean - Han Sol Kim; Ji-Sun Kim; Min Kuk Suh; Mi Kyung Eom; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; Jung-Sook Lee (Archives of Microbiology, 2022)

Marinobacter arenosus sp. nov., a halotolerant bacterium isolated from a tidal flat - Yunjeong Lee; Veeraya Weerawongwiwat; Jong-Hwa Kim; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jung-Hoon Yoon; Ampaitip Sukhoom; Wonyong Kim (Archives of Microbiology, 2022)

Arenibacterium arenosum sp. nov., isolated from sea sand - Jiseon Jeong; Veeraya Weerawongwiwat; Jong-Hwa Kim; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jung-Hoon Yoon; Ampaitip Sukhoom; Wonyong Kim (Archives of Microbiology, 2022)

Collinsella acetigenes sp. nov., an Anaerobic Actinobacterium Isolated from Human Feces, and Emended Description of the Genus Collinsella and Collinsella aerofaciens - Kook-Il Han; Ji-Sun Kim; Mi Kyung Eom; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Seung-Hwan Park; Ju Huck Lee; Se Won Kang; Jam-Eon Park; Byeong Seob Oh; Seoung Woo Ryu; et al. (Current Microbiology, 2021)

Comparison between MGI and Illumina sequencing platforms for whole genome sequencing - Sol A. Jeon; Jong Lyul Park; Seung-Jin Park; Jeong Hwan Kim; Sung-Ho Goh; Ji-Youn Han; Seon-Young Kim (Genes & Genomics, 2021)

An overview of chondrosarcoma with a focus on nanoscale therapeutics - Dong Hyun Kim; Han Sol Lee; Yong-Hyeon Mun; SeokJin Koh; Joon-Sun Park; Sang Min Lee; Nae-Won Kang; Mee Yeon Lee; Cheong-Weon Cho; Dae-Duk Kim; Jae-Young Lee (Journal of Pharmaceutical Investigation, 2020)

Comamonas flocculans sp. nov., a Floc-Forming Bacterium Isolated from Livestock Wastewater - Dong-Hyun Kim; Kook-Il Han; Hae-Jun Kwon; Mi-Gyeong Kim; Young-Guk Kim; Doo-Ho Choi; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jong-Guk Kim (Current Microbiology, 2020)

Stability evaluation of H3N2 influenza split vaccine in drying process for solidification - Sung-Jin Kim; Young-Guk Na; Hong-Ki Lee; Hye-Jin Lee; Miao Wang; Hyun Wook Huh; Han-Sol Lee; Jae-Young Lee; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2020)

Experimental and Numerical Investigation of Self-Burial Mechanism of Pipeline with Spoiler under Steady Flow Conditions - Woo-Dong Lee; Hyo-Jae Jo; Han-Sol Kim; Min-Jun Kang; Kwang-Hyo Jung; Dong-Soo Hur (Journal of Marine Science and Engineering, 2019)
Herein, hydraulic model experiments and numerical simulations were performed to understand the self-burial mechanism of subsea pipelines with spoilers under steady flow conditions. First, scour characteristics and self-burial functions according to the spoiler length-to-pipe diameter ratio (S/D) were investigated through hydraulic experiments. Further, the Navier–Stokes solver was verified. The experimental values of the velocity at the bottom of the pipeline with a spoiler and the pressure on the sand foundation where the pipeline rested were represented with the degree of conformity. Scour characteristics of a sand foundation were investigated from the numerical analysis results of the velocity and vorticity surrounding the pipelines with spoilers. The compilation of results from the hydraulic experiment and numerical analysis showed that the projected area increased when a spoiler was attached to the subsea pipes. This consequently increased the velocity of fluid leaving the top and bottom of the pipe, and high vorticity was formed within and above the sand foundation. This aggravated scouring at the pipe base and increased the top and bottom asymmetry of the dynamic pressure field, which developed a downward force on the pipeline. These two primary effects acting simultaneously under steady flow conditions explained the self-burial of pipelines with a spoiler attachment.

Improvement of cellular uptake of hydrophilic molecule, calcein, formulated by liposome - Su-Min Han; Young-Guk Na; Han-Sol Lee; Gi-Ho Son; Seong-Hoon Jeon; Ki-Hyun Bang; Sung-Jin Kim; Hye-Jin Lee; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2018)

Human-APOBEC3G-dependent restriction of porcine endogenous retrovirus replication is mediated by cytidine deamination and inhibition of DNA strand transfer during reverse transcription - Sae Young Jin; Hyung Yell Choi; Han Sol Kim; Yong-Tae Jung (Archives of Virology, 2018)

Optimization of TILLING system based on capillary electrophoresis for targeted selection of pepper gene mutants - Han Sol Kang; Sang Hoon Kim; Sang Woo Lee; Se Won Kim; Jaihyunk Ryu; Jin-Baek Kim; Seon-In Yeom; Si-Yong Kang; Yeong Deuk Jo (Horticulture, Environment, and Biotechnology, 2018)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Dissipation kinetics, pre-harvest residue limits, and hazard quotient assessments of pesticides flubendiamide and fluopicolide in Korean melon (Cucumis melo L. var. makuwa) grown under regulated conditions in plastic greenhouses - Md. Humayun Kabir; A. M. Abd El-Aty; Md. Musfiqur Rahman; Sung-Woo Kim; Han Sol Lee; Hyung Suk Chung; Jung Ah Do; Ji Hoon Jeong; Byung-Joon Chang; Moon Ik Chang; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Desorption of micropollutant from spent carbon filters used for water purifier - Da-Sol Kwon; So-Yeon Tak; Jung-Eun Lee; Moon-Kyung Kim; Young Hwa Lee; Doo Won Han; Sanghyeon Kang; Kyung-Duk Zoh (Environmental Science and Pollution Research, 2017)

Selective serotonin reuptake inhibitor sertraline inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Han Sol Kim; Hongliang Li; Hye Won Kim; Sung Eun Shin; Il-Whan Choi; Amy L Firth; Hyoweon Bang; Young Min Bae; Won Sun Park (Journal of Biosciences, 2016)

Construction of mutation populations by gamma-ray and carbon beam irradiation in chili pepper (Capsicum annuum L.) - Yeong Deuk Jo; Sang Hoon Kim; Ji-Eun Hwang; Ye-Sol Kim; Han Sol Kang; Se Won Kim; Soon-Jae Kwon; Jaihyunk Ryu; Jin-Baek Kim; Si-Yong Kang (Horticulture, Environment, and Biotechnology, 2016)

Development of serological procedures for sensitive, rapid detection of Cucumber mosaic virus in Lilium - Han Sol Kim; Dong Wan Kim; Yong-Tae Jung (Horticulture, Environment, and Biotechnology, 2016)

Evaluating client application status for V-World Open API service - Han-sol Jang; Dong-kyu Kim; Jung-min Kim; In-sung Jang (Spatial Information Research, 2016)

The class III anti-arrhythmic agent, amiodarone, inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Hongliang Li; Han Sol Kim; Hye Won Kim; Sung Eun Shin; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Amy L. Firth; Young Min Bae; Il-Whan Choi; Won Sun Park (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Spirosoma radiotolerans sp. nov., a Gamma-Radiation-Resistant Bacterium Isolated from Gamma Ray-Irradiated Soil - Jae-Jin Lee; Sathiyaraj Srinivasan; Sangyong Lim; Minho Joe; Seonghun Im; So Il Bae; Kyoung Ryun Park; Ji-Hee Han; Se-Hee Park; Bo-min Joo; Sol-Ji Park; Myung Kyum Kim (Current Microbiology, 2014)